139k views
5 votes
Solve x
8(3x+6)=9(2x−4)

User Freak
by
5.3k points

2 Answers

3 votes

Answer:

x=-14

Explanation:

Expand 8(3x+6)

a=8 b=3x c=6

=8*3x+8*6

Simplify; 8*3x+8*6

=24x+48

Expand 9(2x-4)

a=9, b=2x, c=4

=9*2x-9*4

Simplify;9*2x-9*4

=18x-36

24x+48=18x-36

Subtract 48 from both sides;

24x+48-48=18x-36-48

Simplify;

24x=18x-84

Subtract 18x from both sides;

24x-18x=18x-84-18x

Simplify;

6x=-84

Divide both sides by 6;

6x/6=-84/6

Simplify; 6x/6

=x

Simplify ; -84/6

x=-14

Helped by none other than the ONE & ONLY #QUEEN herself #DRIPPQUEENMO !

User Latata
by
5.6k points
3 votes

Answer: -48

Explanation:

User Shanison
by
5.0k points